La fine del futuro: le trasformazioni del sentimento dell’identità personale e della politica in Italia (Lebenswelt. Aesthetics and philosophy of experience., 2019)
This essay aims to emphasize the link between the feelings of insecurity and uncertainty that spreads in contemporary societies and the rise of populism. The triumph of globalization, the crisis of welfare state caused a social atmosphere of  insecurity and environmental fear: in this situation the citizens mostly fight for individual security and political leaders suggest a simple and schematic conception of democracy.
Keywords: insecurity, uncertainty, self-reliance, populism